Vacinologia reversa e imunoinformática aplicadas à identificação de candidatos vacinais contra Enterobacter cloacae - Soares, Gabriela Guerrera (2025)
Antimicrobial resistance associated with the Enterobacter cloacae complex represents an increasing challenge in hospital settings, especially given the scarcity of effective new antibiotics. Despite the clinical relevance of this pathogen, no licensed vaccines against E. cloacae currently exist, and the therapeutic alternatives available are becoming progressively more limited. In this context, the present study aimed to develop a multi-epitope vaccine candidate capable of inducing both cellular and humoral immune responses against conserved proteins of this pathogen, using a robust pipeline integrating subtractive proteomics, reverse vaccinology, and immunoinformatics. A total of 21 complete clinical genomes were analyzed, enabling the identification of 1,352 proteins associated with essentiality, virulence, or antibiotic resistance, which were subsequently filtered to yield 39 proteins non-homologous to the human proteome and to the gut microbiota. From these, nine promising proteins were selected, and B- and T-cell epitopes were predicted based on high binding affinity to multiple MHC alleles, non-toxicity, absence of allergenicity, and elevated immunogenic potential. These components supported the development of four multi-epitope vaccine constructs (VEC1–VEC4), among which VEC1 exhibited the most favorable characteristics, including optimal physicochemical properties, a stable three-dimensional structure, strong predicted interaction with Toll-like receptors, and an estimated global population coverage of 92.6%. Immune simulations demonstrated the vaccine’s ability to induce robust antibody production, activation of helper and cytotoxic T cells, and formation of memory cells after three simulated doses. Additionally, the VEC1 sequence was codon-optimized for expression in Escherichia coli and successfully cloned in silico into the pET-28a (+) vector, indicating feasibility for future experimental validation. The vaccine candidate developed here shows practical potential for controlling E. cloacae infections, contributing to reduced selective pressure from antibiotics and supporting efforts to combat antimicrobial resistance. These findings highlight the value of immunoinformatics as an accelerating tool in vaccine development and provide a solid foundation for subsequent in vitro and in vivo validation studies.